An Explicit Formula for Symmetric Polynomials Related to the Eigenfunctions of Calogero-Sutherland Models - Hallnäs, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We review a recent construction of an explicit analytic series representation for symmetric polynomials which up to a groundstate factor are eigenfunctions of Calogero-Sutherland type models. We also indicate a generalisation of this result to polynomials which give the eigenfunctions of so-called 'deformed' Calogero-Sutherland type models.